Gold price dynamics under differing economic conditions - Vodolahin, Pavel; Čermáková, Klára; Kotrba, Vojtěch; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
Security and preservation of their savings are of interest to every person. Due to rising inflation, high-interest rates, and escalation of the political situations, people are increasingly thinking about investments to preserve their assets. However, stocks, bonds, and currencies will not always be able to help with this task in problematic times. Thus, the goal of this thesis is to determine whether gold can be considered a safe haven asset in periods of economic recessions. The theoretical part focuses on the causal relationships between the gold price and such variables as the Consumer Price Index of 3 countries: the United States, Germany, and Great Britain, Spot Crude Oil Prices, and Interest Rates of the USA, Great Britain, and Germany. The review of relations is based on the analysis of the scientific works of other authors. A more detailed analysis of the relationship between variables was carried out using an Ordinary Least Squares (OLS) regression model over different time periods. The results showed that the demand for gold and its price increased despite the problematic times. However, gold price changes are not always explained by the same variables as in previous periods. This analysis has potential for future research with the use of different tools to show a complete picture of the influence of elements on the price of gold.
Vedoucí práce: Klára Čermáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses